2008
DOI: 10.1068/a4008rvw
|View full text |Cite
|
Sign up to set email alerts
|

Review: Neoliberal Environments: False Promises and Unnatural Consequences

Abstract: In academic debates about environmental protection and social equity, neoliberalism has supplanted globalization as the newest catchphrase. A growing body of literature on neoliberalism, particularly in the fields of political ecology, political economy, and geography, has shown the concept to be at least as unwieldy as its predecessor. Neoliberal Environments: False Promises and Unnatural Consequences emerges specifically from this expansive proliferation of scholarship with the aim to collect and represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 2 publications
0
20
0
Order By: Relevance
“…Failure on such a scale cannot be resolved by tinkering with policy. While geographers typically attribute such dynamics to neoliberalism (Faber, 2008; Holifield, 2007), this is only part of the story. For instance, what is the connection between court decisions that contract the definition of discrimination and neoliberalism?…”
Section: Environmental Racism and Racial Capitalismmentioning
confidence: 99%
See 2 more Smart Citations
“…Failure on such a scale cannot be resolved by tinkering with policy. While geographers typically attribute such dynamics to neoliberalism (Faber, 2008; Holifield, 2007), this is only part of the story. For instance, what is the connection between court decisions that contract the definition of discrimination and neoliberalism?…”
Section: Environmental Racism and Racial Capitalismmentioning
confidence: 99%
“…Kurtz (2009) has observed that the racial state has been overlooked by EJ scholars. Fortunately, researchers have begun analyzing state programs and practices, showing how the state needs to be problematized (Holifield, 2007; Harrison, 2015; Konisky, 2015). Earlier I presented literature indicating that the state has not seriously sought to intervene in the environmental racism gap.…”
Section: Environmental Racism and Racial Capitalismmentioning
confidence: 99%
See 1 more Smart Citation
“…A suite of other examples similarly call attention to the importance of discourses that position certain locales or populations as "backwards" or "uncivilized", regions as empty or "uninhabited", or ecosystems as "deforested" or "degraded", often making those sites subject to colonial or developmental intervention, or as available for resource exploitation (Daigle, 2018;Davis, 2004;Fairhead and Leach, 1995;Willems-Braun, 1997). Yet other contributions affirm the strength of critical work on discourse in nature-society fields: from analyses focused on neoliberalization discourses in environmental governance (Heynen et al, 2007); to the persistence of Malthusian notions of overpopulation or Hardin's notion of the "tragedy of the commons" (e.g. Ojeda et al, 2019;Robbins, 2012); to Edenic narratives or notions of the "noble savage" (Slater, 1995); or persistent notions of individual responsibility for environmental care (e.g.…”
Section: Attention To Story In Nature-society Work: Foundations and K...mentioning
confidence: 99%
“…Scholars, however, note that state interventions have become less generous and discuss strategies of the state to compel community bodies to redress “the imbalance between private affluence and public poverty” without pursuing policies aimed at wealth redistribution ( Jessop 2002, p. 463; Lawrence, Richards, and Lyons 2013; Parsell and Marston 2016). One consequence is the rise of nonprofit and social enterprises that aim to fill gaps in coverage left by various levels of government (Holifield 2007).…”
Section: Homelessness As a Public Policy And Marketing Concernmentioning
confidence: 99%